Autonomous multi-function floor cleaning robot with zig zag algorithm - J. Lee; A. S. Ab Ghafar; N. Mohd Nordin; F. A. Saparudin; N. Katiran (Institute of Advanced Engineering and Science, 2019)
In this present era, people live a very busy life. People in cities have irregular and long working times. In such a situation a person will always find ways of saving time. Household chores are the ones that are most dreaded upon and cleaning a home tops the list. An autonomous floor cleaning robot is developed to help people to complete their cleaning task. This paper presents the development of an autonomous floor cleaning robot by using Arduino as a platform for processing and controlling the input and output. Autonomous vacuum cleaner robot is designed to make cleaning process become easier compared to using manual vacuum. The idea is basically by having the sensor to detect any object and send the input to Arduino that will control the robot movement. This robot can perform vacuum and wiping task with water spray function. It is also programmed to move in zigzag movement to ensure that the robot can clean all the corner of the house and avoid obstacle autonomously. This robot consists of three ultrasonic sensors, one infra-red (IR) sensor and two brushes in front of it to ensure effective cleaning. It is designed to run on flat surface. This autonomous multi-function floor cleaning robot has lower cost compared to existing vacuum robot on the shelves and is suitable for home and small premise usage.